2005
DOI: 10.4081/ijas.2005.3s.172
|View full text |Cite
|
Sign up to set email alerts
|

Carcass traits of four rabbit genotypes

Abstract: Seventy-three rabbits of four genotypes (A - SIKA maternal line; C - SIKA sire line; AxC - hybrids between line A and C; AxCal - crossbreds between line A and the Californian breed) were used to evaluate the effect of genotype on carcass traits. Rabbits were weaned at 35 days and slaughtered at 93 days of age. Rabbits were fed standard feed mixture ad libitum. The highest live weight at slaughter and dressing percentage was achieved by line C, and the lowest in line A. Hybrids between line A and C exhibited sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
2
0
0
Order By: Relevance
“…In agreement with other authors (Dalle Zotte, 2002;Hernandez et al, 2006;Hulot and Ouhayoun, 1999;Khalil and Al-Saef, 2008;Zgur and Kermauner, 2005) who indicated that selection for growth rate has little effect on meat quality, the pHu and WHC were not significantly influenced by genetic origin of rabbits (Table 2). Meat colour values revealed significant differences between genotypes (P<0.01): meat derived from LP showed lower lightness (L*), higher redness (a*) and yellowness (b*) than HY.…”
Section: Carcass and Meat Qualitysupporting
confidence: 94%
See 1 more Smart Citation
“…In agreement with other authors (Dalle Zotte, 2002;Hernandez et al, 2006;Hulot and Ouhayoun, 1999;Khalil and Al-Saef, 2008;Zgur and Kermauner, 2005) who indicated that selection for growth rate has little effect on meat quality, the pHu and WHC were not significantly influenced by genetic origin of rabbits (Table 2). Meat colour values revealed significant differences between genotypes (P<0.01): meat derived from LP showed lower lightness (L*), higher redness (a*) and yellowness (b*) than HY.…”
Section: Carcass and Meat Qualitysupporting
confidence: 94%
“…Meat colour values revealed significant differences between genotypes (P<0.01): meat derived from LP showed lower lightness (L*), higher redness (a*) and yellowness (b*) than HY. This result suggests that local population furnished less pale meat, as confirmed by the higher C* value (P<0.01) and it was probably due to their higher slaughtering age: the more coloured meat in older animals could be a consequence of a decrease in the oxidative metabolism, correlated with the increase of glycolytic energy metabolism (Dalle Zotte, 2002;Pla, 2008;Zgur and Kermauner, 2005). As regards meat colour traits, significant differences between variances are noted for b* and C* (P<0.05) showing the highest variability in local population parameters.…”
Section: Carcass and Meat Qualitysupporting
confidence: 57%